PENGARUH MEDIA QUIZIZZ DALAM PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA MATERI ANIMALIA KELAS X SMA RK BUDI MULIA PEMATANGSIANTAR T.A 2021/2022 - NIDO JAYA SAMUEL SILALAHI; MASNI VERONIKA SITUMORANG; GUNARIA SIAGIAN (LP2MTBM MAKARIOZ, 2022)
This study aims to determine the effect of using Quizizz media on student biology learning outcomes. This study uses the Quasy experimental method with the Noneequivalent Control Group Design. Sampling using the Purpose sampling technique, namely from students of class X IPA 1 and X IPA 2. In learning the Animalia material, one class is taught using Quizizz media especially at the closing of the lesson, while the other class is given assignments in the form of a resume at the conclusion of the lesson. The instrument used was a multiple choice test with 25 items that had been validated. The data analysis technique used the Shapiro-Wilk test for normality test, and univariate of variance for homogeneity test. Furthermore, to test the hypothesis using the T test, while for improving learning outcomes using the N-gain test. The test results obtained that the comparison of the increase in learning outcomes was higher in the experimental class than the control class, while for hypothesis testing, it was obtained t_count 31,020 > t_table 1,683,. So it can be concluded that there is an effect of using Quizizz media on the biology learning outcomes of students of class X IPA SMA RK Budi Mulia Pematangsiantar.